Effect of zinc oxide nanoparticle supplementation on parasite infection and rumen environment of grazing lambs - Leško, Matej; Bombárová, Alexandra; Petrič, Daniel; Batťányi, Dominika; Komáromyová, Michaela; Königová, Alžbeta; Babják, Michal; Halada, Ľuboš; David, Stanislav; Łukomska, Anna; Pawlak, Piotr; Sidoruk, Pola; et al. (Frontiers in Veterinary Science, 2025)
This study investigated the effect of zinc nanoparticles (ZnO-NPs) on the growth parameters, parasitological status, ruminal fermentation, and histopathology of lambs that were experimentally infected with Haemonchus contortus larvae. The infected lambs were divided into two groups (n = 10/group) and grazed on pasture while being fed one of two diets: a control diet consisting of 350 g/d of a dietary concentrate (CONTROL), and a diet consisting of 350 g/d of concentrate enriched with ZnO-NPs (ZINC). Pasture aboveground plant coverage and plant taxa from phytosociological relevés were used as descriptors to investigate differences in vegetation based on plant medicinal properties and the nutritional value. Communities dominated by plants with medicinal properties were mainly found in the CONTROL group's pasture, while the pasture of the ZINC group contained most plants with outstanding nutritional value. The number of eggs per gram of feces was quantified on days D14, D20, D28, D42, D56, D70, D84, D98, and D107 post-infection. There was a significant decrease in egg shedding from D42 onwards in the ZINC group, and from D56 and D70 onwards in the CONTROL group. The ruminal concentration of ammonia nitrogen (p = 0.018), n-butyrate (p = 0.025), n-valerate (p = 0.002), total protozoa count (p < 0.001), and the enzymatic activities of α-amylase (p < 0.001) and xylanase (p = 0.006) were significantly higher in the ZINC group than in the CONTROL group. The molar proportion of acetate was lower (p = 0.011) in the ZINC group than in the CONTROL group. Morphological observations of the rumen indicated that the homogeneity of the ruminal papillae was slightly impaired, the lamina propria was inflamed, or lymphocytes had infiltrated. In conclusion, the dynamics of gastrointestinal nematode infection were significantly reduced, probably due to the medicinal and nutritional properties of the pasture plants. This effect was also enhanced by the supplementation with ZnO nanoparticles, which possess strong anthelmintic potential.